A cancer-associated, genome protective programme engaging PKCε. (December 2020) - Parker, Peter J.; Lockwood, Nicola; Davis, Khalil; Kelly, Joanna R.; Soliman, Tanya N.; Pardo, Ainara Lopez; Marshall, Jacqueline J.T.; Redmond, Joanna M.; Vitale, Marco; Silvia Martini
Abstract: Associated with their roles as targets for tumour promoters, there has been a long-standing interest in how members of the protein kinase C (PKC) family act to modulate cell growth and division. This has generated a great deal of observational data, but has for the most part not afforded clear mechanistic insights into the control mechanisms at play. Here, we review the roles of PKCε in protecting transformed cells from non-disjunction. In this particular cell cycle context, there is a growing understanding of the pathways involved, affording biomarker and interventional insights and opportunities.